Croatian hotel managers’ attitudes towards environmental management systems: perceived benefits and barriers - Šlogar, Helena; Hrvatin, Stella (Oeconomica Jadertina, 2023)
Researchers have pointed out significant adverse environmental impacts of the hotels and suggested environmental management systems (EMS) as a solution for identifying, managing and mitigating those impacts. EMS are adopted by the top management members based on perceived benefits and implementation barriers. The purpose of this study is to explore the attitudes of general managers from Croatian hotels about perceived benefits of and barriers to EMS implementation. Data was collected with online questionnaires from April to June 2021. Sample included 32 general managers, representing hotels from Istria, Kvarner, North, Central and South Dalmatia. Collected data was analysed using descriptive statistics. Croatian hotel managers perceive improved reputation and sustainable resource governance, followed by cost reductions as the main benefits of EMS. Administrative burden, lack of human resources and lack of knowledge are perceived as the most significant barriers for managers of hotels with implemented EMS, while implementation costs, lack of human resources and infrastructure changes are perceived as considerable barriers by managers from hotels without EMS. The results of this study provide an insight about the perceived benefits and barriers of EMS in Croatian hospitality sector contributing to the field by testing the findings of previous research in different context.